EFISIENSI SERAPAN P DAN HASIL TANAMAN PADI (Oryza sativa L.) PADA BERBAGAI IMBANGAN PUPUK KANDANG PUYUH DAN PUPUK ANORGANIK DI LAHAN SAWAH PALUR SUKOHARJO (MUSIM TANAM II) - Jauhari Syamsiyah; Slamet Minardi; Bayu Winoto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2010)
Title : Efficiency of P Up Take and The Yield of Rice Plant (Oryza sativa L.) with Quail Manure and Inorganic Fertilizer at Paddy Soil, Palur, Sukoharjo (Season II). This research was conducted on January-August 2008. Used Randomized Completely Block Design (RCBD) that arranged in factorial with two factors. The first factor was 3 levels of inorganic fertilizer dosage i.e.: without inorganic fertilizer (A1), urea dosage 150 kg.ha-1, SP-36 dosage 75 kg.ha-1, KCl dosage 50 kg.ha-1, and ZA dosage 50 kg.ha-1 (A2), urea dosage 300 kg.ha-1, SP-36 dosage 150 kg.ha-1, KCl dosage 100 kg.ha-1, and ZA dosage 100 kg.ha-1 (A3). And second factor were 3 levels of quail manure dosage i.e.: without quail manure (O1), quail manure dosage 3 Mg.ha-1 (O2); quail manure dosage 6 Mg.ha-1 (O3). Statistical analysis that used was F test or Kruskal-Wallis test, Duncan Multiple Range (DMR) test at 5% in level, and Correlation test. The research result showed that the highest P uptake efficiency, agronomy efficiency, and the grain dry weight was achieved on 50% of inorganic fertilizer recommendation dosage (urea dosage 150 kg.ha-1, SP-36 dosage 75 kg.ha-1, KCl dosage 50 kg.ha-1, and ZA dosage 50 kg.ha-1) and 6 Mg.ha-1of quail manure treatment (A2O3) in mount of 38.83%, 30.40%, and 6.22 Mg.ha-1 respectively. P uptake efficiency in that treatment was increased as much 13.83% than the same treatment in session I. Generally, the grain dry weight on season II lower than season I. The significant decrease in mount of 2,33 Mg/ha-1 found on treatment of inorganic fertilizer present in 50% of recommendation dosage (urea dosage 150 kg.ha-1, SP-36 dosage 75 kg.ha-1, KCl dosage 50 kg. ha-1, and ZA dosage 50 kg.ha-1) and 3 Mg.ha-1 of quail manure treatment (A2O2). Keywords: quail manure, inorganic fertilizer, uptake efficiency, the dry grain weight paddy